Study of surfactants influence on the noopept releasing from the nasal dosage form - B. S. Burlaka; I. F. Bielenichev; V. V. Hladyshev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
The nasal route of drug administration, as is well known, is characterized by some advantages: absorption rate and rapid onset of therapeutic effect, availability of drug delivery without hepatic first-pass elimination, it is suitable and easily accessible. Earlier a medication for nasal administration with noopept – a low toxic substance with peptide nature without any side effects and high activity has been developed.